Pendampingan Pengorganisasian Dan Edukasi Program Kerja Karang Taruna Desa Sumberjati Jatirejo Mojokerto - Fina Surya Anggraini (BAHRI: Jurnal Pengabdian Kepada Masyarakat, 2024)
This program was motivated by the researchers' concern for community institutions that lack understanding of the importance of community organizations such as youth organizations, this is due to the lack of education on the work program of youth organizations. The problem that arises in the field is that the youth organization has been formed but does not run as it should, it is just a formality, because it does not know the function and how each division works. This service activity aims to provide assistance to the youth organization starting from providing work program education to the formation of the organizational structure of the youth organization which is then approved by the village head. This service uses a PAR (Participatory Action Research) approach with data collection methods including; observation, interview and documentation. The result of this service is the establishment of the Sumberjati Village Youth Organization and is carried out as their respective duties.